RESEARCH ON THE EFFECTIVE PATH OF USING INFORMATION TECHNOLOGY TO CREATE EFFICIENT MATHEMATICS CLASSROOM IN PRIMARY SCHOOL - Jerito Pereira; Jihe Chen; Linfeng Hang; Li Li (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The construction of an efficient mathematics classroom in primary school requires us to use various technical means and advanced design concepts comprehensively. The most important thing is to fully tap and release the inner potential of students through the use of these comprehensive technical means so that students can master knowledge more accurately and efficiently and learn and apply it flexibly. In real life, think about some practical problems with mathematical thinking and mode to carry out creative solutions for a problem. Therefore, under the guidance of information technology, the effective path of efficient primary school mathematics classroom, let us firmly seize the opportunity to develop The Times in the age of information technology and let the student's learning effect further improve.